Nuclear‐encoded chloroplast RNA polymerase sigma factor SIG2 activates chloroplast‐encoded phycobilisome genes in a red alga, Cyanidioschyzon merolae. Issue 20 (10th September 2013) - Fujii, Gaku; Imamura, Sousuke; Hanaoka, Mitsumasa; Tanaka, Kan
Abstract : The phycobilisome (PBS) is a photosynthetic light‐harvesting complex in red algae, whose structural genes are separately encoded by both the nuclear and chloroplast genomes. While the expression of PBS genes in both genomes is responsive to environmental changes to modulate light‐harvesting efficiency, little is known about how gene expression of the two genomes is coordinated. In this study, we focused on the four nuclear‐encoded chloroplast sigma factors to understand aspects of this coordination, and found that SIG2 directs the expression of chloroplast PBS genes in the red alga Cyanidioschyzon merolae . Abstract : Phycobilisome (PBS) genes are found on the chloroplast genome in C. merolae . The PBS gene expression is responsive to environmental light and nitrogen cues. Nuclear‐encoded sigma factors are responsible for the chloroplast transcription. We found the sigma factor SIG2 is responsible for the PBS gene transcription.